2006
DOI: 10.1182/blood-2006-02-004341
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bone marrow and intestine transplantation promotes marrow-derived hematopoietic stem cell engraftment and chimerism

Abstract: Organ allografts have been shown to provide a syngeneic microenvironment for organ-based donor hematopoietic stem cells to maintain long-lasting chimerism after transplantation. We hypothesized that organ allografts would also support engraftment and hematopoiesis of adjunctively infused donor marrow stem cells, syngeneic to organ grafts, in nonmyeloablated recipients. In BN-to-LEW and GFPto-ACI rat combinations, donor bone marrow (BM) infusion together with small intestine transplantation (SITx) under short-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
1
5
0
1
Order By: Relevance
“…Should larger studies reproduce our findings, routine monitoring of mixed chimerism may become a very useful tool for treatment tailoring after intestinal and multivisceral transplantation. These studies might also pave the way for pilot protocols combining bone marrow and intestinal transplantation, such as those established in rodents, to promote donor-specific tolerance (50). …”
Section: Discussionmentioning
confidence: 99%
“…Should larger studies reproduce our findings, routine monitoring of mixed chimerism may become a very useful tool for treatment tailoring after intestinal and multivisceral transplantation. These studies might also pave the way for pilot protocols combining bone marrow and intestinal transplantation, such as those established in rodents, to promote donor-specific tolerance (50). …”
Section: Discussionmentioning
confidence: 99%
“…These functional data, together with the immunohistochemical evidence of activated intestinal stellate cells in situ, strongly suggest that carcinoid-induced fibrosis is a stellate-cell induced phenomenon. It is possible that the "intestinal stellate" cell could be derived from precursor cells in blood stream and there is some evidence that bone marrow-derived cells can migrate into the SI [29] . A study of hepatic stellate cells, however, conclusively identified that these cells were not derived from bone marrow derived fibrocytes [30] .…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Körbling et al reported that recipients of peripheral blood stem cells showed donor-derived hepatocytes up to 7% in liver tissue specimens endothelium by bone-marrow-derived cells [33]. Recently, Nakao et al reported that infused bone marrow stem cells engraft into both the allogeneic marrow environment and the syngeneic extramarrow environment (intestinal graft) [34].…”
Section: Discussionmentioning
confidence: 99%